The Social Capital in Family Firms: Impacts on Family-Longevity-Goals and Performances - Daniel Kurniawan; Elia Ardyan; Istiatin; Luhgianto (The Winners, 2022)
The research was motivated to examine the impact of family, specifically in social capital on firm performances during the COVID-19 pandemic. The research used a quantitative approach and will be analysed by both descriptive and inferential statistics by obtaining questionnaires from the 89 research subjects with a Likert scale to create a whole picture of the social capital dimensions of 89 family firms and their family longevity goals (FLG) as well as their firm performances (FP). The research finds that social capital dimensions have a significant and positive impact on both family longevity goals and firm performance. Moreover, it is found that family longevity goals mediate the positive relationship between social capital dimensions and firm performances. It is also revealed that the impact of social capital dimensions is stronger in firms controlled by the second generation. It is suggested that future research include the external side of the social capital to have further understanding on its impact towards the performance of family business.